ANALISIS STRUKTUR PASAR INDUSTRI KONSTRUKSI DI INDONESIA TAHUN 2007-2011 - Annisa Utami (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2012)
The purpose of this study was to determine how the structure, conduct and performance of the construction industry in Indonesia. And to know how much influence the structure, conduct and performance of the construction industry in Indonesia. Analytical techniques used in this research is to use the Concentration Ratio (CR4) and the Herfindahl-Hirchman index (IHH), which which took the example of 8 Indonesian construction companies wich were tested whithin a period 2007-2011. The results showed the level of concentration ratio (CR4) ranged from 73,02% to 76,16%, then the figure shows the structure of the constraction industry period 2007- 2011 is an oligopoly tight. While based on the Herfindahl-Hirschman index, is the range from 0,159695275 to 0,169852, which means the structure of the construction industry in Indonesia is not a monopoly or not structured approaches 1, when viewed from the level of concentration between the years 2007-2011, it can be concluded that the level of competition in the construction industry in Indonesia is very competitive. it is characterized by the competition of market share among the four dominant companies in the Indonesian construction industry in terms of revenueKeywords: Oligopoly, CR4, IHH, Structure, Conduct and Performance.